Implementation of the 2012 upper secondary school curriculum in Mexico: a 21st-century framework enquiry - Hernández-Fernández, Jimena (2022)
Objective. This study aims to analyze how the new upper secondary school curriculum in Mexico captures 21st-century skills and teachers’ perceptions of success. Method. The design of the study complies a comparison analysis between the Mexican upper secondary school curriculum and a 21st-century skills framework. Additionally, qualitative data on teachers’ perceptions of success is collected through eight focus groups with 72 participants in 4 States of Mexico. Results. The findings show that the curriculum is short in strategies for the development of 21st-century skills. Moreover, although teachers welcome them, they perceive a lack of support and doubt about students’ learning capabilities. Conclusions. Although Mexico has progressed in providing a 21st-century skills learning environment through the new curriculum, the educational system remains with the opportunity to offer a more suitable and adequate framework as well as support and training for teachers.